Juanita Kidd Stout papers - Stout, Juanita Kidd, 1919-1998.
Correspondence, legal case files, speeches, articles, topical files, family papers, scrapbooks, and other papers relating chiefly to Stout's career as a trial judge specializing in murder trials. Documents her service on the Philadelphia County municipal court and court of common pleas and the Pennsylvania supreme court. Other subjects include juvenile delinquency, youth gangs, and welfare. Includes papers of the Chandler, Kidd, and Stout families. Correspondents include Raymond Pace Alexander, Sadie Tanner Mossell Alexander, Anne X. Alpern, Genevieve Blatt, Lawrence L. Boger, David Boren, Jean M. Capers, Mahala Dickerson, John W. Hamilton, William Hastie, Charles Hamilton Houston, Frederica Massiah-Jackson, Gail Nelson, Robert N. C. Nix, Henry Ponder, Leah Sears-Collins, Richard S. Schweiker, Charles Z. Smith, Arlen Specter, and Ronald A. White.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Jurist; first African American female appointed or elected judge of a court of record or general jurisdiction in the U.S.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alexander, Raymond Pace, -- 1898-1974 -- Correspondence; Alexander, Sadie Tanner Mossell, -- 1898-1989 -- Correspondence; Alpern, Anne X. -- Correspondence; Blatt, Genevieve, -- 1913-1996 -- Correspondence; Boger, Lawrence L. -- Correspondence; Boren, David, -- 1941- -- Correspondence; Capers, Jean M. -- Correspondence; Dickerson, M. Ashley -- 1912- -- Correspondence; Hamilton, John W. -- Correspondence; Hastie, William, -- 1904-1976 -- Correspondence; Houston, Charles Hamilton, -- 1895-1950 -- Correspondence; Massiah-Jackson, Frederica A. -- Correspondence; Nelson, Gail -- Correspondence; Nix, Robert N. C. -- 1905-1987 -- Correspondence; Ponder, Henry, -- 1928- -- Correspondence; Sears-Collins, Leah -- Correspondence; Schweiker, Richard S. -- 1926- -- Correspondence; Smith, Charles Z. -- 1927- -- Correspondence; Specter, Arlen -- Correspondence; White, Ronald A. -- Correspondence; Chandler family; Kidd family; Stout family; Pennsylvania. -- Court of Common Pleas (Philadelphia County); Pennsylvania. -- Municipal Court (Philadelphia County); Pennsylvania. -- Supreme Court; Courts -- Pennsylvania; Gangs; Juvenile delinquency; Trials (Murder) -- Pennsylvania; Welfare economics; Jurists